O052 A retrospective analysis of a single-centre experience with administration of neoadjuvant chemotherapy prior to surgical removal of breast tumour. (22nd July 2022) - Reveendran, D; Tait, C; Hogan, B
Abstract: Introduction: Neoadjuvant chemotherapy (NACT) is increasingly used to aid breast preservation surgery for patients with non-conservable disease at presentation. NICE guidelines recommend offering primary systemic therapy to patients with ER- disease and/or HER2+ disease and for those with ER+ disease to reduce tumour size. This retrospective study aimed to analyse the incidence of local and systemic recurrence post NACT. Methods: A retrospective analysis of NACT usage was conducted from January 2011 to December 2020 at the breast surgery unit. Clinical data of patients who received NACT were collected using the local Breast Unit database, Electronic Patient Record (EPR) and Systm1. Data included patient demographics, type of breast and axillary surgical procedure, histopathology of breast tumour, pathological response to NACT and time to local and/or systemic recurrence. Results: 202 patients received NACT for breast cancer between January 2011 to December 2020. Analysis showed an increasing use of NACT ranging from 2.19% of all cancers in 2013 to 14.5% in 2020. 89/202 patients underwent breast preservation surgery. 1 patient developed local recurrence at median follow up of 26 months. 42 patients developed systemic recurrence, and 40 of them had residual disease found at surgery post NACT at median follow up of 24 months. Conclusion: Our unit has been increasingly using NACT over the last 8 years in line with guidance. Breast conserving surgery post NACT is associated with a low risk of local recurrence. The risk of systemic disease progression post NACT is very low for patients who have complete pathological response. Take-home message: Breast conserving surgery post NACT is associated with a low risk of local recurrence. The risk of systemic disease progression post NACT is very low for patients who have complete pathological response.